Discursive Analysis of ‘Yam Theory’: Mapping King Prithvi Narayan Shah’s Essence to Contemporary Geopolitics - Pulami, Manish Jung (Unity Journal, 2022)
In the light of Nepal’s geostrategic location between India and China, its physical geography has been described through several discourses and rhetoric. The discourses produce meanings, and they directly affect the political behaviour of a state. One of the persistent discourses explaining Nepal’s geopolitical situation is “Nepal as a ’yam ‘between two boulders” by King Prithvi Narayan Shah. In that sense, the ‘yam’ theory postulates the geopolitical circumstances of Nepal. The research is guided by the primary question of whether the yam theory is still relevant for Nepal in the present context. Examining the importance of 'yam theory' in the geopolitical circumstances of Nepal, the study aims at discursively analyzing the origin and development of the yam discourse, its importance for understanding and comprehending the geopolitical nature of Nepal, and its essence present in the contemporary and evolving geopolitics. Methodologically, the study adheres to the practices in the discourse analysis process, focusing on the origin and development of the 'yam' theory. Adhering to the constructive and linguistic turn in IR regarding the conceptual framework of the study, the research takes the help of historical documents, journal articles, geopolitical review reports, and commentaries to analyse the yam theory’s geopolitical relevance and relate it to the present geopolitical situation of Nepal. This paper first introduces the scope and the rationale of the topic. Notably, the following section examines the origin of ‘yam’ rhetoric as a ‘discourse’ and development as a‘theory’. Following the arguments from the discursive analysis of ‘yam’, the article then traces its essence in the present geopolitical context for Nepal. In conclusion, this research article identifies the relevance of ‘yam’ for Nepal as the strategy for accommodation, balancing, neutrality and equiproximity.